Age-Related Change in Visual Working Memory: A Study of 55,753 Participants Aged 8–75 - Brockmole, James R.; Logie, Robert H. (Frontiers in Psychology, 2013)
Visual working memory abilities of 55,753 individuals between the ages of 8 and 75 were assessed to provide the most fine-grain analysis of age-related change in visual working memory to date. Results showed that visual working memory changes throughout the lifespan, peaking at age 20. A sharp linear decline follows that is so severe that by age 55, adults possess poorer immediate visual memory than 8 and 9 year olds. These developmental changes were largely explained by changing visual working memory capacity coupled with small short-term visual feature binding difficulties among children and older adults.